2011
DOI: 10.13181/mji.v20i3.446
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution of T cell receptor β gene in Indonesian nasopharyngeal carcinoma patients

Abstract: Abstrak Metode: Penelitian dilakukan dengan teknik PCR-RFLP menggunakan enzim restriksi Bgl II pada gen TCR-β. Analisis PCR-RFLP gen TCR-β digunakan untuk mendeterminasi alotip gen TCR-β pada penderita KNF dan kontrol dan pada kelompok etnis Cina dan pribumi dalam populasi Indonesia. Hasil: Hasil penelitian menunjukkan bahwa distribusi alotip gen TCR-β pada penderita KNF dan kontrol tidak berbeda bermakna (p > 0,05). Frekuensi alel A meningkat pada penderita KNF. Distribusi alotip gen TCR-β antara etnis Cina d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other research has reported that DMPA doses of 1.25 mg/kg body weight could influence gonadotropin and testosterone secretion. 13 The reduction in testosterone that occurs in hypogonadism could activate the mechanism of apoptosis within spermatogenic cells. Research reported that DMPA-treated rats could affect increased apoptosis of spermatogonia (20%), spermatocytes (30%), and 50% of spermatids.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has reported that DMPA doses of 1.25 mg/kg body weight could influence gonadotropin and testosterone secretion. 13 The reduction in testosterone that occurs in hypogonadism could activate the mechanism of apoptosis within spermatogenic cells. Research reported that DMPA-treated rats could affect increased apoptosis of spermatogonia (20%), spermatocytes (30%), and 50% of spermatids.…”
Section: Introductionmentioning
confidence: 99%